Genomic Characterization of Recent Chicken Anemia Virus Isolates in China - Li, Yang; Fang, Lichun; Cui, Shuai; Fu, Jiayuan; Li, Xiaohan; Zhang, Huanmin; Cui, Zhizhong; Chang, Shuang; Shi, Weifeng; Zhao, Peng (Frontiers in Microbiology, 2017)
Chicken anemiavirus (CAV) causes diseases in young chickens, which include increased pathogenicity of secondary infectious agents, generalized lymphoid depletion, and immunodepression. In the present study, we have identified 22 CAV strains isolated from several commercial chicken farms in Northern China during 2014-2015. In addition, two CAVs were also isolated from stray mouse and dog feces, respectively. To our knowledge, this is the first report of identification of CAV from mouse and dog feces. Phylogenetic analysis of 121 full-length CAV genome sequences showed that all available CAV could be classified into eight lineages, supported by phylogenetic trees estimated using different methods. Furthermore, the 24 novel CAV sequences scattered across different branches, lack of clear spatio-temporal distribution characterization. Analysis of the 450 amino acids of VP1 protein identified 33 amino acid substitutions that were specific for CAVs from northern China. Putative gene recombination events were also detected in the genomes of newly isolated CAVs. In particular, a putative recombinant event was detected in the CAV-Dog genome with high statistical support. In summary, we established a robust classification system for CAV, revealed additional genomic diversity of CAV, and therefore, warranted additional efforts to explore CAV genomics and epidemiology.